Development of a model of sustainable development of entrepreneurship in agriculture - Ivanchenko, Vitalii (Technology audit and production reserves, 2020)
The object of research is a model of sustainable development of entrepreneurship in agriculture. The work considers some theoretical foundations of the process of sustainable development and characterizes the main provisions of the model of sustainable development of entrepreneurship in agriculture. The research methodology is based on theoretical and methodological analysis of scientific literature, characteristics of the process of sustainable development and the formation of a model for sustainable development of entrepreneurship in agriculture. Also, description, analysis and modeling are applied and a combinatorial-logical approach is applied to build a formal model of sustainable development of entrepreneurship in agriculture. The research results show that, taking into account the diversity in agriculture and the presence of various forms of management and property, the unifying factor in the process of sustainable development should be a model of sustainable development of entrepreneurship in agriculture. Various forms of farming in the countryside, under the influence of certain institutions and institutions, and using the available land resources, production and human capital, etc., grow agricultural products and ensure the country's food security. The process of sustainable development of entrepreneurship should provide for the use of energy and resource-saving technologies and focus on growing environmentally friendly products with constant social development of the region. This approach, in turn, will provide a multiplier effect, when constant small investments in social and intellectual capital, as a social component of sustainable development, and maintaining the environmental component at an appropriate level, will increase the level of production profitability and the development of the economic component of sustainable development. The practical significance of the research lies in the fact that the research results can be used as a reference material for researchers of entrepreneurship and the process of sustainable development, or for entrepreneurs themselves to plan their activities